A SYSTEMATIC LITERATURE REVIEW OF OVERALL EQUIPMENT EFECTIVENESS IMPELENTATION IN ASIA - Sukma, Dias Irawati; Setiawan, Indra; Purba, Humiras Hardi (Teknik Industri Unikom, 2021)
Overall equipment effectiveness (OEE) is an approach used to measure the productivity of equipment or machines. The aim of this paper is to identify review and analyze the OEE approach. More specific knowledge about OEE has grown rapidly. Much research on OEE is carried out in various industries to measure the productivity of equipment or machines. This paper involves a review study of 30 papers related to OEE implementation in various industries. This paper contains the results of many different aspects. These aspects include focus is an industry. Focus number of distribution by country and focus year of publication. This paper is useful for all types of industrial sectors to find solutions to problems with equipment or machine performance. This paper also provides an advantage for future researchers to add insight and reference for OEE-related studies in various industries.